Insights into the accuracy of social scientists’ forecasts of societal change - Igor Grossmann; Amanda Rotella; Cendri A. Hutcherson; Konstantyn Sharpinskyi; Michael E. W. Varnum; Sebastian Achter; Mandeep K. Dhami; Xinqi Evie Guo; Mane Kara-Yakoubian; David R. Mandel; Louis Raes; Louis Tay; et al. (Nature Human Behaviour, 2023)
How well can social scientists predict societal change, and what processes underlie their predictions? To answer these questions, we ran two forecasting tournaments testing the accuracy of predictions of societal change in domains commonly studied in the social sciences: ideological preferences, political polarization, life satisfaction, sentiment on social media, and gender–career and racial bias. After we provided them with historical trend data on the relevant domain, social scientists submitted pre-registered monthly forecasts for a year (Tournament 1; N = 86 teams and 359 forecasts), with an opportunity to update forecasts on the basis of new data six months later (Tournament 2; N = 120 teams and 546 forecasts). Benchmarking forecasting accuracy revealed that social scientists’ forecasts were on average no more accurate than those of simple statistical models (historical means, random walks or linear regressions) or the aggregate forecasts of a sample from the general public (N = 802). However, scientists were more accurate if they had scientific expertise in a prediction domain, were interdisciplinary, used simpler models and based predictions on prior data.